Case Report of Adult Pulmonary Blastoma: Very rare presentation - Asghar, Asma; Rauf, Muhammad Haris; Sheikh, Ali Zafar; Siddique, Kashif; Hassan, Aamna (Pakistan Armed Forces Medical Journal, 2026)
A case study of a 41-year-old male patient, a known smoker presented with complaints of right-sided chest pain, cough and shortness of breath for two months for which he got a chest X-ray, which revealed soft tissue opacity in the right upper and middle lobe. On examination there were slightly diminished breath sounds over the right hemi thorax. A pulmonary blastoma (PB) diagnosis was confirmed through a biopsy and immunohistochemistry. Diagnostic imaging (CT, MRI, PET-CT) was done as it plays a crucial part in seeing the tumor resectability, treatment response and rule out metastatic disease. Although surgical excision is the treatment of choice in PB but in our case, the tumor was extremely aggressive, progressive and irresectable so chemotherapy was recommended by a multidisciplinary specialized team.